Childhood Fat and Lean Mass: Differing Relations to Vascular Structure and Function at Age 8 to 9 Years. Issue 10 (October 2018) - Sletner, Line; Mahon, Pamela; Crozier, Sarah R.; Inskip, Hazel M.; Godfrey, Keith M.; Chiesa, Scott; Bhowruth, Devina J.; Charakida, Marietta; Deanfield, John; Cooper, Cyrus; Hanson, Mark
Abstract : Objective—: Childhood body mass index (BMI) has been related to vascular structure and function. However, little is known about the differing contributions of fat and lean mass to this relationship. Our objectives were to relate the fat and lean mass (bone excluded) components of BMI (fat mass index and lean mass index; mass [kg]/height [m] 2 ) to vascular measures in prepubertal children. Approach and Results—: In the UK Southampton Women's Survey mother-offspring cohort, 983 children had dual x-ray absorptiometry and vascular measurements at 8 to 9 years. Using linear regression analyses, we found that most vascular measures were related to BMI, but fat and lean mass contributed differently. Systolic blood pressure was positively associated with both fat mass index (β=0.91 [95% CI, 0.52–1.30] mm Hg) and lean mass index (β=2.16 [95% CI, 1.47–2.85] mm Hg), whereas pulse rate was positively associated with fat mass index (β=0.93 [95% CI, 0.48–1.38] b/min) but negatively associated with lean mass index (β=−1.79 [95% CI, −2.59 to −0.99] b/min). The positive relation between BMI and carotid intima-media thickness was mainly due to a positive association with lean mass index (β=0.013 [95% CI, 0.008–0.019] mm). Carotid-femoral pulse wave velocity, but not carotid-radial pulse wave velocity, was positively associated with fat mass index (β=0.06 [95% CI, 0.03–0.09] m/s). For systolic blood pressure, carotid-femoral pulse wave velocity and reactive hyperemia significant interactions indicated that the association with fat mass depended on the amount of lean mass. Conclusions—: In prepubertal children, differences in vascular structure and function in relation to BMI probably represent combinations of adverse effects of fat mass, adaptive effects of body size, and relatively protective effects of lean mass. Abstract : Supplemental Digital Content is available in the text.